Peran Pancasila Dalam Membangun Tatanan Sosial Demokratis Menuju Terwujudnya Masyarakat Madani Indonesia - Arzi Prasetyo; Iksan Rifai; Wisnu Nur Adinata; Zakhy Arya Ramadan (CV. SINAR HOWUHOWU, 2025)
Pancasila as the foundation of Indonesian thought, contains a set of values that serve as the basic guidelines for regulating communal life in this country. This study aims to explain how these values shape a democratic social order as the basis for the emergence of a civil society. The research was conducted by reading and analyzing articles published over the past five years using keywords such as “Pancasila,” “social order,” “democracy,” and “civil society.” From the articles found, 20 articles were selected because they were relevant to the research theme, contained appropriate analysis, and were available in full text. The results of the study show that each principle of Pancasila has moral and social principles that play a role in maintaining fair and rational relationships between people and respecting diversity. The values of humanity, deliberation, and unity have proven to be an important part of strengthening an inclusive public sphere and encouraging responsible citizen participation. The research findings also confirm that the formation of a civil society requires a consistent understanding of the values of Pancasila, both through education and public policies that emphasize justice and openness. Thus, Pancasila is not only the basis of the state ideology, but also a philosophical guide that leads social change towards a civilized, democratic, and just life.